2021
DOI: 10.3389/fpsyg.2021.569133
|View full text |Cite
|
Sign up to set email alerts
|

Can Online Academic Integrity Instruction Affect University Students’ Perceptions of and Engagement in Academic Dishonesty? Results From a Natural Experiment in New Zealand

Abstract: The problem of academic dishonesty is as old as it is widespread – dating back millennia and perpetrated by the majority of students. Attempts to promote academic integrity, by comparison, are relatively new and rare – stretching back only a few hundred years and implemented by a small fraction of schools and universities. However, the past decade has seen an increase in efforts among universities to promote academic integrity among students, particularly through the use of online courses or tutorials. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Fortunately, more training aimed at providing students with the appropriate knowledge has been developed during the last decade. The natural experiment by Dee and Jacob ( 2010 ) described above illustrates one form this training can take, but a number of similar online tools aimed at improving university students’ understanding and raising their awareness of academic integrity issues have recently been developed (e.g., Curtis et al 2013 ; Cronan et al 2017 ; Stephens et al 2021 ). Our results suggest that it might be fruitful to develop similar tools for the upper secondary level.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, more training aimed at providing students with the appropriate knowledge has been developed during the last decade. The natural experiment by Dee and Jacob ( 2010 ) described above illustrates one form this training can take, but a number of similar online tools aimed at improving university students’ understanding and raising their awareness of academic integrity issues have recently been developed (e.g., Curtis et al 2013 ; Cronan et al 2017 ; Stephens et al 2021 ). Our results suggest that it might be fruitful to develop similar tools for the upper secondary level.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is divided into plagiarism, cheating (giving or receiving assistance), fabrication, falsification, misbehaviour, jockey, and collusion in solving improper problems (Farisi, 2013). AD has been observed for thousands of years (Stephens et al, 2021). Many studies have indicated the prevalence of AD in common assessments conducted in an online format (Kennedy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have demonstrated that educational initiatives, such as online modules that focus on academic integrity, can positively impact students’ attitudes, reducing potentially unethical behaviours ( Belter and Du Pré, 2009 ; Ballard, 2013 ; Bealle, 2017 ; Palmer et al, 2019 ; Sefcik et al, 2019 ; Du, 2020 ). Stephens et al (2021) argued, however, that online courses are only partially useful for students, but they can become much more effective within a comprehensive approach to promoting academic integrity. Boehm et al (2009) suggested that providing clear definitions with specific examples of what constitutes unethical behaviours can effectively prevent academic integrity breaches.…”
Section: Introductionmentioning
confidence: 99%